Differential Regulation of T-cell Immunity and Tolerance by Stromal Laminin Expressed in the Lymph Node - Simon, Thomas; Li, Lushen; Wagner, Chelsea; Zhang, Tianshu; Saxena, Vikas; Brinkman, C. Colin; Tostanoski, Lisa H; Ostrand-Rosenberg, Suzanne; Jewell, Chris; Shea-Donohue, Terez; Hippen, Keli; Blazar, Bruce; et al. (Wolters Kluwer Health, 2019)
Background. Stromal laminins α4 and α5 are differentially regulated in transplant tolerance and immunity, respectively, resulting in altered T-cell trafficking. We hypothesized that laminins directly regulated T-cell activation and polarization. Methods. Human and mouse CD4 T cells were activated in Th1, Th2, Th17, or regulatory T cell (Treg) environments with/without laminin α4 and/or α5. Laminin α5 receptors were blocked with anti-α6 integrin or anti-α-dystroglycan (αDG) monoclonal antibodies, and T-cell polarization was determined. T-cell receptor transgenic TEa CD4 cells that recognized donor alloantigen were transferred into C57BL/6 mice that received alloantigen or cardiac allografts. Laminin receptors were blocked, and TEa T-cell migration and differentiation were assessed. Laminin expression was measured in several models of immunity and tolerance. Results. In diverse models, laminins α4 and α5 were differentially regulated. Immunity was associated with decreased laminin α4:α5 ratio, while tolerance was associated with an increased ratio. Laminin α4 inhibited CD4+ T-cell proliferation and Th1, Th2, and Th17 polarization but favored Treg induction. Laminin α5 favored T-cell activation and Th1, Th2, and Th17 polarization and inhibited Treg. Laminin α5 was recognized by T cell integrin α6 and is important for activation and inhibition of Treg. Laminin α5 was also recognized by T cell α-DG and required for Th17 differentiation. Anti-α6 integrin or anti-DG prolonged allograft survival. Conclusions. Laminins α4 and α5 are coinhibitory and costimulatory ligands for human and mouse CD4 T cells, respectively. Laminins and their receptors modulate immune responses by acting as one of the molecular switches for immunity or suppression
Keywords: stromal laminins α4 and α5; CD 4 T cells; molecular switches for immunity or suppression; coinhibitory and costimulatory ligands for human and mouse CD4 T cells